FENOMENA INTERFERENSI BAHASA MELAYU TERHADAP BAHASA INDONESIA PADA MASYARAKAT KELURAHAN TAREMPA KABUPATEN KEPULAUAN ANAMBAS - Agusta, Damara; Malik, Abdul; Suhardi; Doddy irawan; Isnaini Leo Shanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language interference is a common phenomenon in bilingual communities, particularly in areas where local languages are actively used alongside Indonesian. In Tarempa Village, Siantan District, Anambas Islands Regency, the intensive use of Malay in daily communication potentially influences the use of Indonesian. This study aims to describe the forms and types of Malay language interference in Indonesian spoken by the local community. The research employed a descriptive qualitative approach. Data were collected through observation, non-participant observation (Simak Bebas Libat Cakap/SBLC), audio recording, and documentation. The data consisted of spoken utterances containing elements of malay interference. The findings reveal that Malay language interference in Indonesian is predominantly manifested in lexical and phonological forms. Lexical interference appears through the use of Malay vocabulary in Indonesian utterances, while phonological interference is reflected in pronunciation changes influenced by the Malay sound system. These interferences are primarily caused by the community's bilingualism, the dominant use of Malay as the first language, and the close linguistic relationship between Malay and Indonesian. The findings confirm that language contact within bilingual communities significantly contributes to the occurrence of language interference while also reflecting the preservation of local linguistic identity in everyday communication.